« Le noyau atomique/La loi de désintégration radioactive » : différence entre les versions

m
: <math>\frac{d \left( e^{- \lambda_A t} - e^{- \lambda_B t} \right)}{dt} = 0</math>
 
: <math>\frac{d \left( e^{- \lambda_A t \right)} }{dt} - \frac{d \left( e^{- \lambda_B t} \right) }{dt} = 0</math>
 
: <math>\frac{d \left( e^{- \lambda_A t \right)} }{dt} = \frac{d \left( e^{- \lambda_B t} \right) }{dt}</math>
 
: <math>\lambda_A \left( e^{- \lambda_A t} \right) = \lambda_B \left( e^{- \lambda_B t} \right)</math>
 
: <math>\frac{\lambda_A}{\lambda_B} = \frac{e^{- \lambda_B t}}{e^{- \lambda_A t}}</math>
 
: <math>\frac{\lambda_A}{\lambda_B} = e^{(\lambda_A - \lambda_B) t}</math>
 
: <math>\ln{ \left( frac{\lambda_A}{\lambda_B} \right) } = (\lambda_A - \lambda_B) t</math>
 
: <math>t = \frac{\ln{\left(frac{\lambda_A}{\lambda_B}\right)}}{\lambda_A-\lambda_B}</math>
 
====Équilibre séculaire====
40 954

modifications